Synthesis, characterization and antitumor activity of a poly-4-Vinyl pyridine-co-cannabidiol polymer - Fuentes-Ríos, David; Moya-Utrera, Federico; Moreno, Javier; Mesas, Cristina; Doña Flores, Manuel; Sarabia-García, Francisco Ramón; López-Romero, Juan Manuel; Melguizo, Consolación; Prados, José (Elsevier, 2024)
Due to its natural origin and numerous beneficial properties, cannabidiol (CBD), one of the major phytocannabinoids of the Cannabis sativa L., has attracted the attention of many research groups in recent years. In this work, we prepared 4-vinylpyridine (4VP) and CBD co-polymeric nanoparticles (solid@poly-4VP-co-CBD) using N,N’-methylenbisacrylamide (BIS) as cross-linker, and in which CBD is covalently incorporated into the polymeric structure. We evaluated particle morphology by Transmission Electron Microscopy (TEM), while compositional analyses were carried out by Nuclear Magnetic Resonance (NMR) spectroscopy, MALDI mass spectrometry, and Raman and Energy Dispersive X-Ray (EDX) spectroscopies. Moreover, the antitumor effect was analyzed in A549 human lung cell lines, using cell cycle analysis and antiproliferative assays. Interestingly, the polymeric drug retained the cytotoxic and antiproliferative effects of CBD. This fact shows that the solid@poly-4VP-co-CBD system can be considered as a new polymeric drug (PD) and may have an enormous potential since it can make up for the shortcomings of the use of free drugs such as low stability or bioavailability.
Keywords: Química inorgánica; Cancer; Polímeros; CBD co-polymer; CBD solubility; Lung cancer; Polymeric drug